Twórczość Juliusza Słowackiego w ukraińskich czasopismach i drukach zwartych końca XIX i początku XX wieku (1876-1910) - Ciwkacz , Olga (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The publication history of early Juliusz Słowacki’s texts translations is analysed in this article. Translations were made by Ukrainian literature representatives: Olena Pchilka, Vasyl Shchurat, Mykhajlo Starytsky, Ivan Verkhratsky, Volodymyr Kalbo, Volodymyr Stebnytsky, Sydor Tverdokhlib and Mykhajlo Pavlyk. These translations were published in Ukrainian journals of the second half of XIX and beginning of XX century: "Drug", "Dennitsa", "Dilo", "Literaturno-Naukovyj Vistnyk", "Ridnyj Kraj" and in almanacs "Moloda Muza" and "Sich".